Peningkatan Pengetahuan dan Perilaku Pencegahan Penyakit Akibat Perubahan Iklim di Yayasan Bait Al-Qur’an Mulia: Improving Knowledge and Behavior of Disease Prevention Due to Climate Change at the Bait Al-Qur’an Mulia Foundation - Umara, Annisaa Fitrah; Latipah, Siti; Safitri, Rully Angraeni (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Climate change has an impact on the health sector such as triggering diseases. Children are a vulnerable group to diseases caused by climate change. The foundation's education curriculum has not integrated the topic of climate change into learning activities. The attitude of maintaining health levels in the foundation is still limited. The purpose of the service is to improve knowledge and behavior in preventing diseases caused by climate change in the Bait Al-Qur'an Mulia Orphanage Foundation environment. Methods include health checks; education; Focus Group Discussions; and waste management practices. The results of the health checks of students showed an average blood pressure of 104/67 mmHg, weight of 40.97 kg, height of 147.16 cm, BMI of 18.73 kg/m2, and body temperature of 36.51°C. There was an increase in students' knowledge regarding climate change, diseases caused by climate change, and waste management skills. Suggestions are for students and foundation managers to implement sustainable waste management and be actively involved in efforts to prevent diseases caused by climate change.